Association of serum S100B, S100A1 and Zinc-α2-Glycoprotein levels with anthropometric, metabolic and clinical indices in men and women - Kheirouri, Sorayya; Alizadeh, Mohammad; Ebrahimi, Elham; Jabbari, Masoumeh (Progress in Nutrition, 2019)
Objectives: We aimed to investigate serum levels of S100B, S100A1, and Zinc-α2- glycoprotein (ZAG) in men and women and to find association of these proteins with anthropometric, metabolic and clinical indices. Methods: Eighty-eight apparently healthy adults, 43 men and 45 women, participated in the study. The participants’ body mass index (BMI), waist circumference (WC), systolic and diastolic blood pressure (SBP and DBP) were measured. Serum levels of total cholesterol (TC), triglyceride (TG), low and high density lipoprotein cholesterol (LDL-C and HDL-C), fasting blood sugar (FBS), insulin, S100B, S100A1 and ZAG protein were examined by enzymatic and ELISA laboratory methods. Homeostatic model assessment- insulin resistance (HOMA-IR) index was calculated. Results: Serum levels of S100B, S100A1 and ZAG were comparable between men and women groups. S100B protein was positively associated with TG (r= 0.41, p= 0.006), SBP (r= 0.46, p= 0.002), and DBP (r= 0.37, p= 0.02), but negatively with HDL-c in men. Serum levels of S100A1 were significantly and negatively correlated with WC (r= -0.33, p= 0.03), TG (r= -0.37, p= 0.01), insulin (r= -0.31, p= 0.04) and HOMA-IR (r= -0.32, p= 0.03), in women. There was strong positive correlation between serum ZAG and S100A1 levels in both men (r= 0.86, p< 0.0001) and women (r= 0.67, p< 0.0001) groups. Conclusion: The findings suggest that S100B and S100A1 proteins might have gender-specific activity or regulation. Visceral obesity attenuates S100A1 protein in serum, while enhancement of S100A1 leads to improved metabolic status in women. In contrary, S100B increases with visceral obesity and increment of this protein aggravates metabolic status and blood pressure in men. Positive correlation between S100A1 and ZAG indicates that these two proteins may act in a same biological pathway.